1971
DOI: 10.1515/zna-1971-0810
|View full text |Cite
|
Sign up to set email alerts
|

Elektrische Transportgrößen von n- und p-ZnSb

Abstract: Single-phase Pr 2 CBr was prepared by heating a mixture of PrBr 3 , Pr and C (1 : 5:3) to 1140 • C for 18 d. The crystal structure was investigated by X-ray single crystal diffraction (space group P6 3 /mmc, a = 3.8071 (3), c = 14.7787(12)Å). In the structure the Pr atoms form C-centered octahedra condensed into Pr 2 C sheets via common edges; these sheets are separated by the Br atoms which are in a trigonal prismatic environment of Pr atoms. Pr 2 CBr is a black shiny compound with metallic conductivity. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1985
1985
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…If numerous p-doping elements (such as Ag, Cu, Sn) are known to improve the figure of merit of ZnSb, it is trickier to synthetize n-type ZnSb. It is possible to obtain temporary n-type ZnSb by Ga, In or Te doping in single crystals, but they turn into p-type after a certain period of time 42 . Explanations for this phenomenon could be the migration of oxygen in the sample 43 or zinc acting as acceptors (similarly to what has been suggested in CdSb 44 ).…”
Section: Znsb Dopingmentioning
confidence: 99%
See 1 more Smart Citation
“…If numerous p-doping elements (such as Ag, Cu, Sn) are known to improve the figure of merit of ZnSb, it is trickier to synthetize n-type ZnSb. It is possible to obtain temporary n-type ZnSb by Ga, In or Te doping in single crystals, but they turn into p-type after a certain period of time 42 . Explanations for this phenomenon could be the migration of oxygen in the sample 43 or zinc acting as acceptors (similarly to what has been suggested in CdSb 44 ).…”
Section: Znsb Dopingmentioning
confidence: 99%
“…This explains why mostly all the n-type ZnSb samples have been reported for single crystals. However, with time, these samples are oxidized and ZnO is formed 32 increasing thus the amount of zinc vacancies in the sample which will lead eventually to an n-type → p-type transition 42 .…”
Section: B N-type Doping With Ga and Inmentioning
confidence: 99%
“…Ce phénomène était jusqu'à présent passé inaperçu, principa¬ lement à cause de la discrétion de l'espèce, de la difficulté à en observer de grandes séries et du caractère peu spectaculaire des variations. Plusieurs auteurs s'étaient d'ailleurs étonnés d'une telle homogénéité morphologique chez une espèce à distribution relictuelle et morcelée (Müller & Schneider, 1971 ;Klemmer, 1972: Bruno, 1980Bodinier, 1981 ;Delaugerre, 1981a ;Rieppel & Schneider, 1981). Camerano (1904), en dépit de l'approche avant-gardiste de son analyse, ne disposait pas des outils statistiques modernes qui nous ont permis, quatre-vingts ans plus tard, de mettre en évidence une différence morphologique sensible entre les deux populations étudiées par cet auteur.…”
Section: -Discussionunclassified
“…Cette distribution, presque entièrement macro et micro-insulaire, est composée d'une série d'isolats géographiques. En nous basant sur les données de Capocaccia (1956), Müller & Schneider (1971), Vanni & Lanza (1978, Bruno (1980) et Delaugerre (1981b, nous avons dénombré 127 isolats peuplés par le Phyllodactyle d'Europe. Ces isolats sont de tailles très inégales, depuis une grande île comme la Sardaigne jusqu'à des rochers de quelques centaines de mètres carrés seulement.…”
unclassified
“…The influence of impurities has also to be considered when looking at the results available in the literature. Muller et al [62] and Abou-Zeid et al [20,63] reported the influence of oxygen on the thermoelectric properties of tellurium doped ZnSb single crystals. Indeed, during the material preparation, the use of hydrogen is compulsory to obtain n-type material.…”
Section: Tellurium Diffusion: Znsb-te Diffusion Couplementioning
confidence: 99%